JAVMA News (Journal of the American Veterinary Medical Association, 2013)
Carbapenem-resistant Enterobacterales (CRE) are an emerging, multidrug-resistant threat to human and animal health. Emergence is driven by antimicrobial use and multidirectional transmission pathways between humans, animals, and the environment. Carbapenems are essential drugs for treatment of multidrug-resistant infections in humans and, although not approved for veterinary use, are infrequently prescribed in dogs and cats in an extralabel manner. In the US, CRE detections in companion animals have recently increased. While prevalence of CRE in US companion animals is estimated to be low, outbreaks in veterinary hospitals demonstrate that CRE can be transmitted within animal healthcare settings, persist in the environment, and cause operational disruption. Exchange of CRE between companion animals and people has been documented. There are several important knowledge gaps about CRE in companion animals, including (1) uncertainties in true prevalence due to infrequent testing and underreporting; (2) lack of understanding of carbapenem resistance mechanisms because of inconsistent access to testing; (3) limited data on colonization dynamics; and (4) lack of information characterizing risk factors for acquisition. A coordinated One Health approach for surveillance and preparedness is essential to identify, prevent, and contain CRE. Here we provide veterinary professionals with a comprehensive, practical overview of CRE epidemiology, mechanisms of resistance, diagnostic considerations, therapeutic limitations, and infection prevention and control (IPC) practices. The companion Currents in One Health article by Frey et al, AJVR, forthcoming 2026, reviews the current understanding of carbapenemase-producing CRE in companion animals; identifies gaps in epidemiology, diagnostics, and infection control; and outlines priorities for future research.